Music Creations Hyang | Tabuh Kreasi Hyang - I Ketut Andre Aldi Wijaya (GHURNITA: Jurnal Seni Karawitan, 2023)
Hyang is an innovative musical creation inspired by parhyangan, one of the Tri Hita Karana concepts as local wisdom (local genius) found in Balinese society. This work is made by still using traditional patterns, and also develops according to the musical elements of the stylist's interpretation. The spoken medium used in this work is the Semaradana gamelan with the addition of two Gong Gede Saih Pitu musicians. In realizing this work, the creation method offered by Alma M. Hawkins in her book Creating Thriugh Dance (1064) is used, that the arrangement of a work of art is carried out through three stages, namely Exploration (exploration), Improvisation (improvisation) and Forming (formation). . This book was translated by Y. Sumandiyo Hadi into his book entitled "Creating Through Dance". This work uses the Tri Angga structure which consists of pengwit, pengawat, designer. Where this work is inspired by the life of the Balinese people whose daily rituals are in the context of their relationship with God. This piece is presented by 19 musicians with a total duration of 11 minutes.